Intraosseous Rosai‐Dorfman disease diagnosed by touch imprint cytology evaluation: A case series. Issue 1 (23rd August 2017) - Pendse, Avani A.; Wobker, Sara E.; Greene, Kevin G.; Smith, Scott V.; Esther, Robert J.; Dodd, Leslie G.
Abstract: Sinus histiocytosis with massive lymphadenopathy, also known as Rosai‐Dorfman disease (RDD) is a rare benign disorder that primarily affects the lymph nodes. Localized lymphadenopathy is the most common clinical manifestation of this disorder. However, RDD has been described in several extra‐nodal sites including the head and neck region, soft tissue, skin, upper respiratory tract, gastro‐intestinal tract and central nervous system (CNS). Involvement of the bone is considered very rare, occurring in less than 10% patients. RDD is one of the histiocytoses and the differential diagnosis includes entities such as Langerhans cell histiocytosis and Erdheim‐Chester disease. In the rare intraosseous variant, the clinical and radiologic differential diagnosis is broader and includes neoplasms such as osteosarcoma and Ewing sarcoma. In this report, we describe three cases of extra‐nodal, intraosseous RDD where touch imprint cytology played a crucial role in diagnosis. Two of the cases initially presented with involvement of the head and neck region and later developed intraosseous disease; while the third patient presented with primary bone involvement. The diagnosis was established by core biopsy with touch imprints of the bone lesions. The cytologic samples showed numerous histiocytes, often with neutrophils within their cytoplasm (emperipolesis) in addition to lymphocytes and plasma cells. The diagnosis of RDD was confirmed with appropriate immunohistochemical stains. Our account of these three cases of intraosseous Rosai‐Dorfman disease highlights the role of cytology in the diagnosis of this rare entity.